Bioimpedance and Dual-Energy X-ray Absorptiometry Are Not Equivalent Technologies: Comparing Fat Mass and Fat-Free Mass - Lopes, Sofia; Fontes, Tatiana; Tavares, Rejane Giacomelli; Rodrigues, Luis Monteiro; Ferreira-Pêgo, Cíntia (International journal of environmental research and public health, 2022)
Bioimpedance (BIA) is the most frequently used technology for body composition assessment at a daily clinical level, mostly due to its low price and user-friendly operation. However, many doubts persist regarding its physiological meaning and applicability. The present study aimed to compare one BIA system and the Dual-Energy X-ray Absorptiometry (DXA) for the characterization of body composition in a previously selected cohort of healthy adult participants. A descriptive observational cross-sectional study included a final sample of 121 participants, 93 women and 28 men, with a mean age of 28.26 ± 9.72 years old and a mean body mass index (BMI) of 22.68 ± 3.13 kg/m2. Statistics involved paired t-tests and agreement analysis by the Bland-Altman method. BIA underestimated the percent body fat (%BF) by 5.56% and overestimated Fat-Free Mass (FFM) by 2.90 kg. A strong positive correlation between both technologies was found for FFM (r = 0.980) and the %BF (r = 0.932), but the disagreement was statistically significant (p < 0.001). Although DXA and BIA seem to correlate, these technologies are not congruent. Therefore, the risk of (mis)interpretation and bias is clear with BIA, potentially impacting the nutritional planning of clinical dietitians and the further results of its patients.